2023
DOI: 10.1177/25152564231181020
|View full text |Cite
|
Sign up to set email alerts
|

IP3R at ER-Mitochondrial Contact Sites: Beyond the IP3R-GRP75-VDAC1 Ca2+ Funnel

Abstract: Membrane contact sites (MCS) circumvent the topological constraints of functional coupling between different membrane-bound organelles by providing a means of communication and exchange of materials. One of the most characterised contact sites in the cell is that between the endoplasmic reticulum and the mitochondrial (ERMCS) whose function is to couple cellular Ca2+ homeostasis and mitochondrial function. Inositol 1,4,5-trisphosphate receptors (IP3Rs) on the ER, glucose-regulated protein 75 (GRP 75) and volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 123 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Similarly, AX also possessed significant intermolecular interaction with these crucial amino acids, indicating the great potential to inhibit channel activity. Certainly, mitochondrial Ca 2+ uptake also depends on VDAC1, which is responsible for the transport of Ca 2+ between cytoplasm and matrix and plays a fundamental role in Ca 2+ homeostasis. , Moreover, VDAC1 triggers mitochondria-mediated apoptosis in the form of oligomerization and induces mitochondria dysfunction. , It has been proved that VDAC1 exists in different oligomer states including monomers, dimers, trimers, tetramers, hexamers, and higher-order oligomers, of which the vital contact site in dimeric VDAC1 involves β-strands 1, 2, and 19. In this study, although the protein expression level of VDAC1 was not significantly affected by AX, the molecular docking results showed that AX was able to act on VDAC1 oligomerization by interacting with the key domain of VDAC1 through hydrophobic interactions and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, AX also possessed significant intermolecular interaction with these crucial amino acids, indicating the great potential to inhibit channel activity. Certainly, mitochondrial Ca 2+ uptake also depends on VDAC1, which is responsible for the transport of Ca 2+ between cytoplasm and matrix and plays a fundamental role in Ca 2+ homeostasis. , Moreover, VDAC1 triggers mitochondria-mediated apoptosis in the form of oligomerization and induces mitochondria dysfunction. , It has been proved that VDAC1 exists in different oligomer states including monomers, dimers, trimers, tetramers, hexamers, and higher-order oligomers, of which the vital contact site in dimeric VDAC1 involves β-strands 1, 2, and 19. In this study, although the protein expression level of VDAC1 was not significantly affected by AX, the molecular docking results showed that AX was able to act on VDAC1 oligomerization by interacting with the key domain of VDAC1 through hydrophobic interactions and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, mitochondrial Ca 2+ uptake also depends on VDAC1, which is responsible for the transport of Ca 2+ between cytoplasm and matrix and plays a fundamental role in Ca 2+ homeostasis. 76,77 Moreover, VDAC1 triggers mitochondria-mediated apoptosis in the form of oligomerization and induces mitochondria dysfunction. 78,79 It has been proved that VDAC1 exists in different oligomer states including monomers, dimers, trimers, tetramers, hexamers, and higher-order oligomers, 80 of which the vital contact site in dimeric VDAC1 involves β-strands 1, 2, and 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation